Biomarkers for Predicting Left Atrial or Left Atrial Appendage Thrombus in Anticoagulated Patients with Nonvalvular Atrial Fibrillation. (20th June 2020) - Zhou, Xue; Wang, Zuolan; Dou, Shuang; Chen, Kangyin; Liu, Enzhao; Liu, Tong; Li, Guangping; Che, Jingjin
Abstract : Purpose . Although atrial fibrillation (AF) is often associated with thromboembolic complications, there is no definite biomarker for detecting the presence of thrombi in the left atrial (LA) or left atrial appendage (LAA) in patients with nonvalvular atrial fibrillation (NVAF). Methods . NVAF patients who underwent transesophageal echocardiography (TEE) to evaluate LA/LAA thrombus and spontaneous echo contrast (SEC) before AF ablation were included. Multivariate logistic regression and receiver operating characteristic curve (ROC) analyses were performed to explore the independent risk factors of LA/LAA thrombus and indicate the best cutoff point. Results . Of the 260 consecutive subjects (mean age: 63.67 ± 9.39 years; 42% women), 45 (17.3%) patients were with LA/LAA thrombus, 131 (50.4%) were with SEC, and 84 (32.3%) were with neither thrombus nor SEC. The results of multivariate logistic regression analysis showed that N-terminal pro-B-type natriuretic peptide (NT-proBNP) (OR, 2.179; 95% CI: 1.191–3.987; p = 0.012 ) and red cell distribution width (RDW) (OR, 2.398; 95% CI: 1.075–5.349; p = 0.033 ) were independently correlated with the presence of LA/LAA thrombus but not D-dimer (OR, 0.999; 95% CI: 0.998–1.000; p = 0.210 ). When all patients were divided into four groups based on the combination between RDW (cutoff value: 12.95%) and NT-proBNP levels (cutoff value: 368.9 ng/L), the rate of LA/LAA thrombus was the highest in the high RDW and NT-proBNP group. Conclusion . In anticoagulation patients with NVAF, elevated NT-proBNP and RDW are related to LA/LAA thrombus. Therefore, these might be considered as useful prognostic markers in the management and treatment of NVAF patients.